2018
DOI: 10.3762/bjoc.14.29
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of RGD and isoDGR peptidomimetic-α-amanitin conjugates for tumor-targeting

Abstract: RGD-α-amanitin and isoDGR-α-amanitin conjugates were synthesized by joining integrin ligands to α-amanitin via various linkers and spacers. The conjugates were evaluated for their ability to inhibit biotinylated vitronectin binding to the purified αVβ3 receptor, retaining good binding affinity, in the same nanomolar range as the free ligands. The antiproliferative activity of the conjugates was evaluated in three cell lines possessing different levels of αVβ3 integrin expression: human glioblastoma U87 (αVβ3+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 38 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…The linker type has only a minimal effect, conjugates with uncleavable linker displayed a slightly reduced affinity, presumably because of the shorter linker between the ligand and the drug. Similar results were reported for analogous conjugates of the cyclo [DKP‐RGD] and cyclo [DKP‐ iso DGR] ligands and paclitaxel or α‐amanitin . In addition, high selectivity for α v β 3 integrin was reported for cyclo [DKP‐RGD]‐paclitaxel conjugates involving various lysosomally cleavable Val−Ala or GFLG linkers .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The linker type has only a minimal effect, conjugates with uncleavable linker displayed a slightly reduced affinity, presumably because of the shorter linker between the ligand and the drug. Similar results were reported for analogous conjugates of the cyclo [DKP‐RGD] and cyclo [DKP‐ iso DGR] ligands and paclitaxel or α‐amanitin . In addition, high selectivity for α v β 3 integrin was reported for cyclo [DKP‐RGD]‐paclitaxel conjugates involving various lysosomally cleavable Val−Ala or GFLG linkers .…”
Section: Resultssupporting
confidence: 81%
“…The resulting alkyne‐functionalized activated linker 8 was conjugated to cryptophycin‐55 glycinate by forming a carbamate to give compound 9 . The PEG4‐containing azido‐functionalized cyclo [DKP‐RGD] and cyclo [DKP‐ iso DGR] ligands were prepared as previously reported . Final conjugation was achieved by copper(I)‐catalyzed azide−alkyne cycloaddition (CuAAC “click” reaction) between compound 9 and cyclo [DKP‐RGD]‐PEG4‐azide or cyclo [DKP‐ iso DGR]‐PEG4‐azide, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies by us revealed colocalization of an RGD‐cryptophycin‐52 conjugate with lysosomes in WM‐115 cells (overexpressing α v β 3 ) and in contrast, an RGD‐cryptophycin‐55 conjugate was internalized both by M21 (overexpressing α v β 3 ) and M21L (α v knockout) cells . Likewise, cytotoxic RGD‐α‐amanitin conjugates did not provide specific uptake . It was further demonstrated that a monomeric RGD‐doxorubicin conjugate afforded good binding affinities toward α v β 3 in a cell adhesion assay, but was not internalized .…”
Section: Methodsmentioning
confidence: 98%
“…Conjugates of the functionalized integrin ligands 5 and 6 with the antimitotic drug paclitaxel (PTX) were synthesized featuring a self‐immolative spacer and the lysosomally cleavable Val‐Ala (VA) linker . More recently, ligands 5 and 6 were bound to the RNA polymerase II inhibitor α‐amanitin via a 6′‐ether, giving cyclo [DKP‐RGD]‐VA‐α‐amanitin and cyclo [DKP‐ iso DGR]‐VA‐α‐amanitin conjugates . Cell viability assays indicated a slightly increased cytotoxicity of the cyclo [DKP‐ iso DGR]‐VA‐α‐amanitin conjugate relative to the free drug …”
Section: Introductionmentioning
confidence: 99%